ANALYSIS OF HORMONAL CHANGES DURING DIFFERENT OVARIAN STIMULATION PROTOCOLS USED IN ART PROGRAMS - Mamadalieva D. M. (Modern American Journals, 2025)
Despite the diverse results of studies and meta-analyses regarding the effectiveness of individual drugs, analysis of data on folliculogenesis and oogenesis shows that LH levels during ovarian stimulation have a significant impact on the quality of oocytes and the likelihood of successful embryo implantation. Studies show that insufficient LH content can negatively affect reproductive outcomes. The article presents the results of a comparative analysis of various methods of ovulation stimulation. The choice of ovarian stimulation protocol in ART programs should be based on consideration of the hormonal status of the patient. The optimal LH content and the combination of gonadotropins contribute to improving the quality of oocytes, the success of fertilization and pregnancy.
Keywords: Infertility, ovulation stimulation, hormonal status, human menopausal gonadotropin, recombinant gonadotropins, assisted reproductive technology protocols.